The effect of dietary energy density and porcine somatotropin on apparent digestibility and retention of nutrients in finishing swine - Stoner, G.R.; Schricker, B.R.; Nelssen, Jim L.; Goodband, Robert D.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixteen barrows were used in a metabolism study (avg wt of 101.2 lb) to evaluate the effect of dietary energy density and porcine somatotropin (pST) on apparent digestibility and retention of nutrients in finishing pigs. This study was designed as a split-plot with 4 mg pST/d or placebo injection as whole plot treatments and four dietary energy densities (1.37, 1.48, 1.60, and 1.71 Meal ME/lb) and period as the subplot treatments. Increasing dietary energy density increased apparent digestibility of dry matter, gross energy, and nitrogen, but had no effect on nitrogen retention. Porcine somatotropin administration had no effect on apparent digestibility of nutrients; however, percentage nitrogen retention was increased 42% compared to control pigs.
Keywords: Swine; Porcine somatotropin; Nitrogen retention; Pig; Digestibility